An exploration the determinants of service quality in healthcare and antecedents of patient healthcare-seeking behavior in Vietnam - Đỗ Huy Lượng; Nguyễn Minh Đức; Nguyễn Ngọc Duy Phương (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Khoa học Xã hội)
Although numerous service quality scales have been developed, relatively few exist specifically for measuring healthcare service quality. Furthermore, studies constructing an integrated conceptual model encompassing factors beyond service quality influencing patients’ intentions to seek medical care are scarce. Drawing upon the HEALTHQUAL model, social cognitive theory, the theory of planned behavior, and the health belief model, this study proposes an integrated model to assess the quality of health services and the antecedents of patients’ intentions to seek medical treatment. The model includes the following factors: service quality, satisfaction, subjective norms, self-efficacy, perceived barriers, and perceived threats, all of which impact behavioral intentions and, ultimately, patients’ decisions to seek medical treatment. This theoretical framework provides a scientific basis and appropriate research directions for future studies related to health services.